A Review on Lung Cancer Treatment Based on Theories of Huangdi Neijing - Niu, Siyue; Wei, Hui; Wei, Dan (Journal of Contemporary Medical Practice, 2026)
This paper aims to explore the diagnosis and treatment of lung cancer combined with theories of Huangdi Neijing (Huangdi’s Internal Classic). By analyzing discussions on human physiology and pathology, zang-fu organs and meridians, as well as the relationship between healthy qi and pathogenic factors recorded in Huangdi Neijing, this paper excavates its guiding significance for the etiology, pathogenesis, clinical manifestations, syndrome differentiation and treatment, health preservation and prevention of lung cancer. It provides theoretical basis and innovative clinical thinking for the TCM treatment of lung cancer, so as to promote the application and development of traditional TCM theories in the treatment of modern malignant tumors.